THE COMPARATIVE STUDY OF GRAMMAR TRANSLATION METHOD (GTM), TASK BASED LANGUAGE TEACHING (TBLT) AND CONTEXTUAL LEARNING TEACHING (CLT) IN WRITING SENTENCES AT SMP SWASTA NURUL ILMI - LUBIS, RAYENDRIANI FAHMEI (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2016)
This research is designed by quantitative research. In this research, participants were Nurul Ilmi students in VIII grade of junior high school. They are 40 students. The instrument used in this research is a test. In this research, the researcher would be applied two tests. They are pre-test and post-test. The technique of data analysis, the researcher used Two Ways Anova. The value of hypothesis testing was 0,000 with opportunity 0,05. Based on the accounting result of the research, so the hypothesis that Grammar Translation Method (GTM), Task Based Language (TBLT) and Contextual Learning Teaching (CTL) have significant difference in writing sentence was could be accepted.